Innovation in Learning to Read the Yellow Book Through the Amtsilati Method in Dormitory "I" Pondok Pesantren Ngalah Sengonagung Purwosari Pasuruan - Nisa, Intan Ulyaun; Mohtarom, Ali; Yusuf , Achmad; Kirom , Askhabul (Literacy: Journal of Education and Social Science, 2024)
This study aims to determine the innovation of learning to read the yellow book through the amtsilati method in Dormitory I of the Ngalah Islamic Boarding School, The approach used is qualitative with data collection techniques through observation, interviews, and documentation. The results of the study showed that the innovation of learning to read the yellow book through the amtsilati method of dormitory I was effective in improving the learning outcomes of students. In addition, it was found that to achieve more optimal results, it is necessary to minimize the existing shortcomings. Overall, the innovation of learning to read the yellow book through the amtsilati method has succeeded in increasing the completeness of student learning outcomes. This finding has important implications for the innovation of learning models in Islamic boarding schools.